An investigation of technology-dependent shopping in the pandemic era: Integrating response efficacy and identity expressiveness into theory of planned behaviour - Wang, Xueqin (2022)
The COVID-19 pandemic has led to a rapid surge of digitalisation in shopping activities. Although the rising phenomenon of technology-dependent shopping is sensational, the subtle motivations that cause such a phenomenon remain to be explored. Thus, extending the theory of planned behaviour (TPB), this study investigates two distinct motivations (i.e. to respond to health concerns and to express self-identity) that lead to technology-dependency among modern shoppers. A survey instrument is adopted for data collection online targeting adult shoppers in Singapore, and the data (n = 519) are analysed using structural equation modelling. Results reveal that the two motivations mediate the relationship between subjective norm/perceived behavioural control and shoppers’ behavioural intention. The response- and identity-mediated paths lead to differentiated behavioural consequences: the former is associated with only shoppers’ engagement intention with shopping technologies, whereas the latter also instigates the habit of technology-dependent shopping. The findings contribute to the TPB framework by confirming the mediator role of two context-specific motivations. The revealed habit formation process of technology-dependent shopping provides practical implications in managing the retailer-shopper relationship in the pandemic era.